LEGAL PROTECTION OF CREDITORS ON THE TRANSFER OF FOUR-WHEEL VEHICLES BY THE DEBTOR TO THIRD PARTIESIN PEKANBARU CITY - Zulfikri Zulfikri; Suryanto Sagala (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
In a fiduciary agreement, the object used as the object of the fiduciary guarantee is still in the control of the owner of the object (the debtor). case it is the granting of property rights to the fiduciary collateral. object without displaying a physical object. In general, in the law of guarantees whose objects are movable objects, the debtor cannot transfer, pledge or lease to other parties the objects that are the object of the Fiduciary Guarantee. This type of research is a sociological legal research conducted by means of a survey, namely research directly to the research location using a data collection tool in the form of interviews. Meanwhile, if viewed from its nature, this writing is descriptive analytical. Legal Protection Against Creditors for the Transfer of Four-Wheel Vehicles by Debtors to Third Parties in Pekanbaru City that the Fiduciary Guarantee Act has attempted to provide a technical protection for the interests of creditors, the implementation of protection through execution of fiduciary guarantees, which in the end provides choices for creditors to take peaceful way which means providing additional costs. Obstacles in Legal Protection Against Creditors on Transfer of Four-Wheel Vehicles by Debtors to Third Parties in Pekanbaru City that the Fiduciary Guarantee Law has given creditors a weak position, such as the lack of firmness in execution and concerning the implementation of executions.